Cloning, sequencing, and expression of the gene encoding Clostridium paraputrificum chitinase ChiB and analysis of the functions of novel cadherin-like domains and a chitin-binding domain. - Morimoto, K (1997)
The Clostridium paraputrificum chiB gene, encoding chitinase B (ChiB), consists of an open reading frame of 2,493 nucleotides and encodes 831 amino acids with a deduced molecular weight of 90,020. The deduced ChiB is a modular enzyme composed of a family 18 catalytic domain responsible for chitinase activity, two reiterated domains of unknown function, and a chitin-binding domain (CBD). The reiterated domains are similar to the repeating units of cadherin proteins but not to fibronectin type III domains, and therefore they are referred to as cadherin-like domains. ChiB was purified from the periplasm fraction of Escherichia coli harboring the chiB gene. The molecular weight of the purified ChiB (87,000) by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis, was in good agreement with the value (86,578) calculated from the deduced amino acid sequence excluding the signal peptide. ChiB was active toward chitin from crab shells, colloidal chitin, glycol chitin, and 4-methylumbelliferyl beta-D-N,N'-diacetylchitobioside [4-MU-(GlcNAc)2]. The pH and temperature optima of the enzyme were 6.0 and 45 degrees C, respectively. The Km and Vmax values for 4-MU-(GlcNAc)2 were estimated to be 6.3 microM and 46 micromol/min/mg, respectively. SDS-PAGE, zymogram, and Western blot analyses using antiserum raised against purified ChiB suggested that ChiB was one of the major chitinase species in the culture supernatant of C. paraputrificum. Deletion analysis showed clearly that the CBD of ChiB plays an important role in hydrolysis of native chitin but not processed chitin such as colloidal chitin.